Inner Circle English Cultural Senses Found in Interlanguage XII - Rycha Rany Susanto; Ignatius Harjanto (Widya Mandala Surabaya Catholic University, 2014)
The learning of culture is unavoidable in the learning of English since cultural values are embedded in the body of language. In order to communicate effectively, language learners need to be culturally aware of what their utterances might convey. As one of important factors in successful language learning process, English course books should foster English cultural issues and support learners to be culturally competence. The study investigated cultural contents of the inner-circle English countries in an English course book entitled Interlanguage XII, which has been approved by Badan Standar Nasional Pendidikan (BSNP). The inner-circle English cultural contents were investigated through the theory of four senses of culture by Adaskou et al (1990). The all four senses of culture were included in Interlanguage XII. The results indicated that the highest percentage is the presence of pragmatic sense, while the least sense was the sociological sense. The results also showed that even though the all four sense were present, the frequency among those four was not balance. This implies the aim and the emphasis of the course book in the foreign language learning; the course book emphasize more on the use of language instead of its grammatical and structural skill.